Information sharing on effects of exposure to building materials in adaptation projects / Sabarinah Sh Ahmad ... [et al.] - Ahmad, Sabarinah Sh; Isnin, Zarina; Yahya, Zaharah; Mohd Salleh, Mustapha (Universiti Teknologi MARA Cawangan Selangor, 2018)
Research findings confirm the existence of hazardous and toxic substances in most building materials. There is limited studies and information on building materials and the effects to health and safety. This study develops an evaluation method that is used to identify the presence of hazardous substances from building materials and assess their public health impact. The information allows stakeholders to identify potential risks and could improve knowledge sharing on building materials information on health and safety in the built environment industry.